THE CONCEPT OF “DISCOURSE” IN LINGUISTICS AND ITS LINGUISTIC INTERPRETATION (Conferencea, 2022)
This article is devoted to study discourse and its importance in literature. Many linguistics discussed about definitions of discourse and also gave some important and valuable information for discourse